1985
DOI: 10.1111/j.1752-1688.1985.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

CHANNEL FORM AND STREAM ECOSYSTEM MODELS1

Abstract: A system is proposed to classify running water habitats based on their channel form which can be considered in three different sedimentological settings: a cobble and boulder bed channel, a gravel bed channel, or a sand bed channel. Three physical factors (relief, lithology, and runoff) are selected as state factors that control all other interacting parameters associated with channel form. When these factors are integrated across the conterminous United States, seven distinct stream regions are evident, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 34 publications
3
63
0
2
Order By: Relevance
“…Mean stream width and depth were 7.5 m (2.0-23.3 m) and 0.26 m (0.04-1.50m), respectively. Stream substrata were primarily gravel, and streams had riffle-pool channel morphology (Brussock et al 1985). Preliminary data suggested that these streams represented a gradient in total P (TP) concentration.…”
Section: Natural P Gradient Of Streamsmentioning
confidence: 99%
“…Mean stream width and depth were 7.5 m (2.0-23.3 m) and 0.26 m (0.04-1.50m), respectively. Stream substrata were primarily gravel, and streams had riffle-pool channel morphology (Brussock et al 1985). Preliminary data suggested that these streams represented a gradient in total P (TP) concentration.…”
Section: Natural P Gradient Of Streamsmentioning
confidence: 99%
“…Patterns of periphyton and macroinvertebrate community structure show similar variation, within and among streams, because their distribution is greatly influenced by habitat structure (Brussock et al 1985;Huryn and Wallace 1987;Lowe and Pan 1996). As a consequence, the habitat-template approach (Southwood 1988) has been effective in predicting patterns of spatial and temporal variability in stream community structure (Scarsbrook and Townsend 1993;Townsend et al 1997a;Biggs et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Moore's Creek is a spring-fed second-order stream that is a part of the Illinois River basin in northwest Arkansas. The headwater streams of the Illinois River basin have alluvial gravel, riffle-pool geomorphology (Brussock et al, 1985). Streams substrates in this river basin are dominated by limestone, sandstone, and shales and have a karst topography.…”
Section: Study Site Descriptionmentioning
confidence: 99%